Optimization of CO2 Laser Engraving Parameters for SiO2-Based Ceramic Materials: Simulation and Experimental Investigation - Nguyen, Thanh Dong; Vu, Toan Thang; Vu, Thanh Tung; Pham, Duc Quang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The use of SiO2 ceramic materials is increasingly prevalent in both industrial and artisanal craftsmanship. These materials exhibit excellent mechanical properties, making them challenging to process, especially after firing. The paper explores the application of CO2 lasers for engraving ceramic materials, addressing challenges in traditional processing methods and offering insights into optimizing laser parameters for enhanced engraving performance. Through simulations using COMSOL Multiphysics software and experimental validations, the thermal interaction between CO2 lasers and SiO2 ceramic substrates is thoroughly investigated. Parameters such as power, scanning speed, pulse width, and repetition frequency are examined to understand their influence on engraving depth, resolution, and surface quality. The research compares continuous wave (CW) and pulsed modes, highlighting their advantages and limitations. The most suitable set of technological parameters is selected for experimentations on unfired and fired ceramic samples. The results demonstrate the effectiveness of CO2 lasers in engraving ceramics and their potential for various industrial applications. This research provides comprehensive insights into applying CO2 laser technology to ceramic materials.